A novel acute medicine virtual ward managing multiple acute medical pathologies: a pilot study in the district general hospital setting - Caroline Dawson; Rahul Sethi; Rosemary Ho; Usman Ahmed; Tahira Adnan (Future Healthcare Journal)
Background: Virtual wards are increasingly used to deliver specialist care remotely through telehealth. The NHS Virtual Ward Operational Framework suggests that its potential could include reducing length of hospital stay and improving patient experience.1 An acute medicine virtual ward pathway was launched in a district general hospital in London designed to use telehealth to manage a variety of acute medical problems remotely. The full inclusion criteria are shown in Fig 1. Each patient meeting these criteria who consented for inclusion was provided with observation monitoring equipment and a sim-enabled device to input their readings into an electronic monitoring platform. Patients unable to use the electronic monitoring platform were eligible for telephone monitoring. Each patient had a management plan of monitoring parameters with the frequency tailored to their acute problem. These also included parameters for escalation. There were three levels of escalation depending on the severity of the derangement: Level 1 would result in advice from an acute medical consultant in-hours; Level 2 would result in advice from an acute medicine consultant in-hours or from the on-call medical registrar out-of-hours; and Level 3 would result in escalation to 999. Patients were discharged from the virtual ward once the discharge criteria were met. Aim: To describe the feasibility and safety of a novel acute medicine virtual ward managing multiple acute medical pathologies. Methods: Clinical data were collected retrospectively for all patients enrolled in the virtual ward within the first 6 weeks of the pathway being launched. This included demographic data, source of referral, the primary acute medical problem being monitored, length of stay, number of contacts and whether each patient required escalation of care. Descriptive statistics was used to summarise the clinical and demographic characteristics of this cohort. Results: 43 patients were enrolled into the virtual ward programme over a 6-week period. The primary acute medical issue being monitored is shown in Table 1. Of these patients, 24 (56%) were female. The mean age was 48.7±19.7 years. Mean length of stay was 4.0±1.8 days. The mean number of contacts per patient was 13.0±5.7. Overall, 38 (88%) patients were enrolled using the electronic monitoring platform and the remaining five were enrolled via telephone monitoring. One patient was discharged from the virtual ward pathway because the team was unable to contact the patient. Eight (19%) patients required escalation during their enrolment, and five (12%) required escalation to the medical registrar, with their symptoms resolved with remote medication adjustment. Two (5%) attended and were discharged from the emergency department. One (2%) patient required hospital admission. Conclusion: Our study shows that a single virtual ward set-up presents a potentially feasible and safe method to reduce length of hospital stay. Further patient recruitment is required to assess this more robustly and allow for cost-effectiveness analysis to determine any potential cost savings.